2019
DOI: 10.1051/sicotj/2018054
|View full text |Cite|
|
Sign up to set email alerts
|

Arabic translation and validation of three knee scores, Lysholm Knee Score (LKS), Oxford Knee Score (OKS), and International Knee Documentation Committee Subjective Knee Form (IKDC)

Abstract: Aim of the work: Translation and validation of three commonly used knee scores to Arabic language: the Lysholm Knee Score (LKS), the Oxford Knee Score (OKS), and IKDC Subjective Knee Form. Methods: Our work focused on translation and validation of the LKS, OKS and IKDC. Construct validity was assessed by comparing the LKS, OKS, and IKDC Subjective Knee Form and previous Arabic translated version of Knee injury and Osteoarthritis Outcome Score (KOOS). Test−retest reliability, internal consistency, and construct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(45 citation statements)
references
References 29 publications
4
41
0
Order By: Relevance
“…Our sample population demonstrated various knee problems, including meniscus or cartilage lesions, multi-ligament injuries, and patellofemoral disorders; nevertheless, almost half of our population (26/55 patients) had at least an ACL injury (it was for them the LKSS was initially designed). Other studies of LKSS cultural adaptation have also used patient groups with various knee problems [8,17,18]. It is interesting that three studies with isolated ACL injuries have demonstrated a Cronbach's alpha similar to ours (between 0.72 and 0.77) [14,16,20]; two studies with various knee problems have shown a Cronbach's alpha between 0.68-0.90 [17,18], and one study including only patellofemoral disorders had a Cronbach's alpha of 0.91 [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our sample population demonstrated various knee problems, including meniscus or cartilage lesions, multi-ligament injuries, and patellofemoral disorders; nevertheless, almost half of our population (26/55 patients) had at least an ACL injury (it was for them the LKSS was initially designed). Other studies of LKSS cultural adaptation have also used patient groups with various knee problems [8,17,18]. It is interesting that three studies with isolated ACL injuries have demonstrated a Cronbach's alpha similar to ours (between 0.72 and 0.77) [14,16,20]; two studies with various knee problems have shown a Cronbach's alpha between 0.68-0.90 [17,18], and one study including only patellofemoral disorders had a Cronbach's alpha of 0.91 [8].…”
Section: Discussionmentioning
confidence: 99%
“…Both scores have been used in numerous publications worldwide, and their reliability, validity, and responsiveness have been established for various knee problems, including ACL and meniscal injuries [3,6,7], patellofemoral pain syndrome [8], medial patellar plica syndrome [9], patellar dislocation [10], various chondral disorders [11], knee arthroplasty [12], as well as in individuals with normal knees [13]. So far, both questionnaires have been translated, validated, and culturally adapted into several different languages, and they have all shown good internal consistency, test-retest reliability, and external validity [6,8,[11][12][13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…A part of the online survey was an Arabic validated version of the International Knee Documentation Committee's (IKDC) subjective knee evaluation form [15]. The IKDC was validated for an assessment of knee function after an ACLR [16].…”
Section: Subjective Knee Functionmentioning
confidence: 99%
“…3; To (1) study and compare the factors Swedish orthopaedic surgeons and physiotherapists consider important for recommending ACLR, and (2) to assess how important orthopaedic surgeons and physiotherapists consider their own and each other's, as well as patients', roles are in the treatment decision (Study III). 4; To (1) describe the key characteristics of treatment decisions for patients with an ACL injury; what treatment was chosen, when was the decision made, which reasons do patients and orthopaedic surgeons state that the treatment decision was based upon, and (2) compare key patient reported function measures (preinjury activity level, knee joint instability and function at baseline, 4 weeks and 3 months after an ACL injury) between patients who had ACLR and those who had non-operative treatment (Study IV)…”
Section: ;mentioning
confidence: 99%
“…Their results were not included in the assessment of the results of the testing of measurement properties. For some other studies 4,54,58,62,67,121,124 , we assigned a poor methodological score one or more measurement properties, but fair to excellent methodological score for the other measurement properties. Thus, these studies were included in the assessment of the results, for the measurement properties where they had a fair to excellent methodological score.…”
Section: Systematic Review Of the Measurement Properties Of The Ikdc-skfmentioning
confidence: 99%